Festival as Cultural Diplomacy: Kurultáj and Its Implementation in Hungary - Pratama, Cakra Diaz; Utomo, Ario Bimo (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2024)
Diplomatic endeavours encompass a range of strategies, including the organisation of cultural festivals, which serve not only as a means of engaging a broader audience but also as platforms for expressing a nation’s identity. One notable example is the Kurultáj festival, which took place in Hungary under the auspices of the Magyar Turán AlapÃtvány. This festival exemplifies the practice of cultural diplomacy, attracting participation from various Central Asian nations. Through cultural diplomacy, participating countries aim to promote their respective national interests within the framework of the Kurultáj festival. This article examines the implementation of the Kurultáj festival between 2008 and 2022, focusing specifically on its association with neo-propagandist cultural diplomacy. It argues that the Kurultáj festival cannot be solely categorised as a manifestation of neo-propagandist cultural diplomacy.